Electromagnetic fields theory of electrical machines Part 1: Poynting theorem for electromechanical energy conversion - Mukerji, SK; Basu, KP; Bhooshan, S; Goel, SK (2004)
The power flow across a closed surface containing moving media is considered using the Poynting theorem. Various components of this power are identified with known expressions. The effects of hysteresis are considered in a linearized form by assuming hypothetical relations between field vectors. These relations result in elliptical hysteresis loops for sinusoidal time-varying fields. The treatment presented may be useful to students preparing for a master's degree or final year bachelor's degree.